1999
DOI: 10.1097/00005373-199909000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Drug Use in Victims of Life-Threatening Trauma

Abstract: These data suggest that alcohol and drug use is associated with life-threatening injury, especially intentional injury. Prevention of substance abuse is essential for the prevention of trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 22 publications
6
74
0
Order By: Relevance
“…For example, pooled data on 4,063 patients treated at 6 regional trauma centers indicated that 40.2% of patients had a positive blood alcohol concentration at admission [5]; when polydrug use (alcohol, illicit drugs) was included, over 60% of the patients tested positive for intoxicants. [6] These findings reflect the results of Cromwell et al [7] who investigated the prevalence of substance use among victims of major trauma presenting to a Level I trauma center. Of the 516 patients who had urine toxicology and blood alcohol screens, 71% screened positive for alcohol or drugs or both: 52% had positive alcohol screens; and 42% had positive drug screens with cocaine and opiates representing 91% of positive drug screens.…”
Section: Substance Use and Injury Among Adultssupporting
confidence: 87%
“…For example, pooled data on 4,063 patients treated at 6 regional trauma centers indicated that 40.2% of patients had a positive blood alcohol concentration at admission [5]; when polydrug use (alcohol, illicit drugs) was included, over 60% of the patients tested positive for intoxicants. [6] These findings reflect the results of Cromwell et al [7] who investigated the prevalence of substance use among victims of major trauma presenting to a Level I trauma center. Of the 516 patients who had urine toxicology and blood alcohol screens, 71% screened positive for alcohol or drugs or both: 52% had positive alcohol screens; and 42% had positive drug screens with cocaine and opiates representing 91% of positive drug screens.…”
Section: Substance Use and Injury Among Adultssupporting
confidence: 87%
“…12 Youth with assault-related injury are at high risk for reinjury. [13][14][15][16][17][18] Sims et al 19 found violently injured youth admitted to trauma units have readmission rates as high as 44% due to assault and 20% mortality due to homicide over a 5-year follow-up; retrospective chart reviews note similar rates. [19][20][21][22][23][24] The ED is the primary medical setting for injured adolescents, [25][26][27][28] and an important setting for violenceprevention programs.…”
mentioning
confidence: 99%
“…3,4,17 In order to more definitively characterize the role of alcohol consumption in trauma, other studies have addressed injury at the level of the individual, analyzing serum alcohol and toxicology data from patient admissions. [18][19][20][21] This work has demonstrated higher odds ratios of trauma among those with elevated blood alcohol level upon hospital admission, particularly for head and facial trauma. Madan et al found that 80% of assault victims and 63% of those in motor-vehicle accidents admitted to a level 1 U.S. trauma center had positive serum ethanol screens, although this study found no significant difference in injury severity score (ISS), length of stay, or mortality between groups with positive and negative screens.…”
Section: Introductionmentioning
confidence: 72%
“…For those who were screened, mean BAL also did not vary among type of trauma or age group, as was expected given previous work linking alcohol availability to unintentional and intentional trauma among various age groups. 3,16,[18][19][20] The trend for increasing BAL during late-night hours (8 pm-6 am) was not significant, reinforcing the importance of a direct measure of alcohol use among trauma victims. Gruenewald and Ponicki and Livingston considered motor vehicle crashes or assaults in their respective studies to be alcohol related if they occurred after 8 pm, while our findings suggest a possible trend, it is clear that such a proxy is not adequate to determine the involvement of alcohol in trauma.…”
Section: Discussionmentioning
confidence: 93%